2019
DOI: 10.1136/annrheumdis-2019-215355
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines shape a changing DNA methylome in monocytes mirroring disease activity in rheumatoid arthritis

Abstract: ObjectiveRheumatoid arthritis (RA) is a chronic systemic autoimmune disease that mainly targets joints. Monocytes and macrophages are critical in RA pathogenesis and contribute to inflammatory lesions. These extremely plastic cells respond to extracellular signals which cause epigenomic changes that define their pathogenic phenotype. Here, we interrogated how DNA methylation alterations in RA monocytes are determined by extracellular signals.MethodsHigh-throughput DNA methylation analyses of patients with RA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…IFNα from the IFN type 1 family has been shown to induce DNA methylation changes in monocytes in vitro [103]. Taken together, these data imply that the epigenetic alterations of the IFN type I genes in several cell types are likely to be a consequence of an aberrantly active IFN-I pathway in SLE.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 79%
See 1 more Smart Citation
“…IFNα from the IFN type 1 family has been shown to induce DNA methylation changes in monocytes in vitro [103]. Taken together, these data imply that the epigenetic alterations of the IFN type I genes in several cell types are likely to be a consequence of an aberrantly active IFN-I pathway in SLE.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 79%
“…Methylation levels in those regions were largely reversible during patient evolution over time. These associations made it possible to generate a predictive mathematical model to estimate patient activities from DNA methylation values [103].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Those alterations, which occur in regions that are functionally associated with inflammatory pathways, are common to those previously observed in other inflammatory diseases. In particular, enriched functional categories of inflammation, immune cell activation and cytokine signalling are also found in RA [6,28,29], SLE [30,31], asthma [32] and IBD [33] in comparable studies, supporting the idea that UA shares epigenetic similarities with other inflammatory diseases and thus can be molecularly considered as such. Furthermore, the identification of vast DNA methylation differences at the TNF locus as well as alterations at several CpGs within the HLA class II region (both at the DMP and DVP level) reasserts UA as an arthritide, such as RA, with which shares clinical characteristics [7,3436]…”
Section: Discussionmentioning
confidence: 74%
“…Epigenetic alterations are associated with both genetic and environmentally-driven determinants which can in turn characterize pathogenic phenotypes. Specifically, DNA methylation and histone modifications, that are altered in multiple pathological contexts, are proposed to be both a causal factor [5] and a consequence of disease [6], as well as an intermediary for genetic susceptibility [7]. In all cases, the exhaustive study of these alterations through high-throughput technologies allows a detailed description and identification of novel molecular pathways that undergo alterations in a pathogenic context.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been demonstrated that changes in the monocyte methylome reflects disease activity in RA patients. Indeed, some CpG sites of STAT3, FPR2, and TNFAIP8 correlate with DAS28 in RA monocytes [168]. However, the authors did not find any significant correlation between patient treatments (either biologic drugs or csDMARDs) and DNA methylation in RA monocytes.…”
Section: The Effect Of Epigenetic Factors On Bdmards Response In Ramentioning
confidence: 82%